Photophysics and X-ray Structure of Crystalline 2-Aminopurine - Neely, Robert K.; Magennis, Steven W.; Parsons, Simon; Jones, Anita C. (Chemphyschem, 2007)
To explore the effect of intermolecular interactions on the photophysics of 2‐aminopurine (2AP) in a well‐defined environment, we have investigated the fluorescence properties of single 2AP crystals, having determined their X‐ray structure. In the crystal, 2AP is subject to base‐stacking and hydrogen‐bonding interactions similar to those found in DNA. The crystal shows dual fluorescence: π‐stacked molecules in the bulk of the lattice have redshifted excitation and emission spectra, while molecules at defect sites have spectra similar to those of 2AP in solution or in DNA. Heterogeneous intermolecular interactions in the crystal give rise to multiexponential fluorescence decay characteristics similar to those observed for 2AP‐labelled DNA. The presence of about 13 % of the 7H tautomer in the crystal confirms that 9H–7H tautomerisation of 2AP occurs in the ground state. Long‐wavelength excitation of a 2AP‐labelled oligonucleotide duplex produced redshifted emission similar to that observed in the crystal, indicating that π‐stacking interaction of 2AP with nucleobases gives rise to a low energy excited state. Interbase interactions in DNA are mimicked in the crystal lattice of 2‐aminopurine, a fluorescent analogue of adenine (see picture). π‐stacking interaction between 2‐aminopurine molecules in the crystal produces a low‐energy excited state, showing redshifted emission.